Performance and capital structure of IPOs in Pakistan from 2000 to 2015 - Attiya Yasmin Javid; Henna Malik (Financial Innovation, 2016)
Background: When a privately owned firm or privatized government entity raises capital by selling its stocks for the first time to general public, is known as initial public offering (IPO). The underpricing phenomenon and ownership structure are important characteristics of IPO process that significantly affect the short-run and long-run performance of private firm and privitized entity. This study compares the short-and long-run performance, and factors affecting these performances for both private IPOs and privatized IPOs in Pakistan. It further investigates the relationship between capital structor and initial underpricing for both group of IPOs. Methods: Event study methodology is used to compares short- and long-run performance spanning from March 2000 to June 2015 of two categories of IPOs issued in the Karachi Stock Exchange (KSE). Multivariate regression analysis is applied to examine the factors that affect the short-run and long-run performance as well as for investigating the relationship betwen underpricing and ownership structure for both group of IPOs. Results: We find that both categories outperform in IPOs at which they are offered to investors on first day of trading, although differences in mean are insignificant. Over a five-year buy-and hold strategy, privatizing IPOs outperform and private IPOs underperform returns on the benchmark KSE 100 Stock Index. The results reveal that the size of the private firm or government entity, aftermarket risk of IPOs, and subscription ratio are significantly associated with the underpricing of IPO shares brought to market. First-day returns, market volatility and retained ownership are associated with higher five-year performance. We find that the concentration of ownership is similar, for both categories of IPOs; and significantly positive related to underpricing. The size of the firm/entity, aftermarket risk, return on assets and subscription ratio also affect ownership concentration. Conclusions: Same level of underpricing in both private and privatized IPOs reveals that Pakistan's government is committed to its privatization policies as they developed capital markets by underpricing of IPOs. To make dispersion in ownership structure and to involve more small investors, the regulatory authorities such as Securities and Exchange Commission of Pakistan (SECP are required to take some steps to minimize concentration in ownership structure. There is a need of some specific range of underpricing by issuers and SECP.
Keywords: G14; G24; G32; 650; Initial public offering; Underpricing; Aftermarket performance; Private owned firms; Public owned firms; Capital structurePakistan